PENGEMBANGAN MODEL PEMBELAJARAN BERDIFERENSIASI BERBASIS KOMUNITAS BELAJAR UNTUK MENINGKATKAN HASIL BELAJAR PADA MAPEL BAHASA INDONESIA SISWA KELAS 3 SEKOLAH DASAR KECAMATAN DUMBO RAYA - Ayu; Rusmin Husain; Rusdin Djibu (LP2M IAIN Sultan Amai Gorontalo, 2025)
This research aims to develop differentiated teaching modules based on learning communities to improve student learning outcomes. The research uses the Research and Development (R&D) method with the ADDIE development model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The approach used is a mix-method, which is a combination of qualitative and quantitative approaches. The results of the study show that the teaching modules developed have gone through a validation process by material and media experts with